A broader context for understanding the basis for and application of wildlife value orientations - Teel, Tara L., author; Manfredo, Michael, advisor; Vaske, Jerry, committee member; Bright, Alan, committee member; Slater, Michael, committee member (Colorado State University. Libraries, 2004)
This dissertation presents two papers that contribute to our theoretical understanding and application of the concept of wildlife value orientations. The concept has emerged as a way of representing the diversity of values that people hold toward wildlife. It has been applied in a number of contexts, but little attention has been devoted to understanding the basis for wildlife value orientations and to determining if they are somehow linked, at a broader level, to cultural and environmental forces. This dissertation uses data from a survey of residents in six western states to address these issues. The first paper builds upon prior research which suggests wildlife value orientations are part of an individual's hierarchical belief structure. Specifically, they are believed to be based on fundamental values and to in turn form a foundation for more specific wildlife-related attitudes and behaviors. In exploring the extent to which wildlife value orientations are related to other cognitions, paper one reveals a relationship between a utilitarian versus protection orientation toward wildlife and Materialist/Post-Materialist values. Individuals with a Materialist value set were more likely than Post-Materialists to have a utilitarian orientation toward wildlife. Paper one also demonstrates the predictive validity of an overall model containing both values and wildlife value orientations in explaining variation in support for wildlife management actions. The second paper expands upon the notion that wildlife value orientations are part of a broader cultural context. It applies the concept of wildlife value orientations as well as Materialist theories of cultural change to explore the factors that may be related to declines in hunting participation in the U.S. The paper examines the relationship between hunting and certain societal-level factors believed to be indicative of forces associated with modernization and in turn related to value shift in this country. Findings revealed a strong positive relationship between active participation in hunting and possession of traditional values, defined by a Materialist values set and a utilitarian orientation toward wildlife. Results also showed that active participation in hunting is related to urbanization, income, education, and residential stability at the state level.
Keywords: recreation